The aspects of human action - Račić, Domagoj (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Anthropological differences assumed by neoclassical economics and macro- sociology and contrasted in the dichotomy of ‘homo economicus’ and ‘homo sociologicus’ are essentially generalisations of the ultimate distinction in the concepts of human action. A corresponding divide also pervades the conceptualisation of institutions. Maximising behaviour and a fixed and independent preference function on the one hand, and adaptive behaviour, and flexible but socially influenced preferences on the other, signify not only characterisations of possible courses of interpretation and action, but also the ‘ideal types’ assumed by the mainstream of the respective disciplines. This work aims to challenge this divide by linking the concepts of rational and interpretive action in the context of the ‘agency and structure’ or ‘participant – social whole’ debates. That is done through providing several new or recontextualised answers at the basic level of individual understanding and interpretation of purposes of action in general, and the action taking place within institutional and organisational contexts in particular. The underlying intention is to present an analytically separable ‘interface’ that links individuals and institutions. This interface is subsequently analysed in terms of four interrelated aspects of human action – habituation, deliberation, participation and reification, and constitution of norms. The paper attempts to offer insights into their internal dynamics of these processes, and to explore the links between them, including their simultaneity, partial overlapping and inherent tensions. Keywords: Human Action; Communities of Practice; Institutions; Habits; Norms Index: 1. Introduction – 2. Human action – 3. The aspects of human action – 4. Habituation – 5. Deliberation – 6. Participation and reification – 7. Constitution of norms – 8. Concluding remarks – References